Bladder Cancer Chemopreventive Agents: Current Knowledge and Concepts - Khajeh, N. R.; Khoyilar, C.; Wu, Y.; Spradling, K.; Zi, X.; Youssef, R.F. (Mini Reviews in Medicinal Chemistry, 2018)
Bladder cancer is the most prevalent malignancy of the urinary tract and is associated with significant morbidity and mortality. Preventative efforts to reduce the medical and financial burdens of bladder cancer are highly desirable. However, the utilization of natural and pharmaceutical products for the prevention and treatment of bladder cancer remains largely controversial. Herein, we review the current body of evidence surrounding a number of natural dietary substances and their roles in chemoprevention of bladder cancer. Possible chemopreventative properties of several pharmaceutical agents are also reviewed. Overall, the current body of evidence is insufficient to establish a clear link between these proposed chemopreventive agents and risk of bladder cancer.
Keywords: Bladder cancer